Frequency of Tumor Necrosis Factor-α, Interleukin-6, and Interleukin-10 Gene Polymorphisms in Mexican Patients with Diabetic Retinopathy and Diabetic Kidney Disease - Patricia Elvira Sánchez-Valencia; Juan Daniel Díaz-García; Margarita Leyva-Leyva; Fabiola Sánchez-Aguillón; Nelly Raquel González-Arenas; Jesús Guillermo Mendoza-García; Erika Karina Tenorio-Aguirre; Mercedes Piedad de León-Bautista; Aurora Ibarra-Arce; Pablo Maravilla; Angélica Olivo-Díaz (Pathophysiology)
Background/Objectives: Two of the microvascular complications in type 2 diabetes (T2D) are diabetic retinopathy (DR), which is the most common cause of non-traumatic blindness, and diabetic kidney disease (DKD); the latter generally requires renal replacement therapy. The aim of the present study was to determine the frequency of polymorphisms of Tumor Necrosis Factor-α, interleukin-6, and interleukin-10 (TNF-α, IL-10, and IL-6), as well as to describe the clinical and laboratory characteristics of T2D association with these microvascular complications. Methods: This study included 203 patients with T2D, of which 102 had microvascular complications: 95 with DR, 50 with DKD, and 15 with diabetic neuropathy (the latter were not included in the statistical analysis); those with T2D without confirmed microvascular complications were considered as controls. Clinical and laboratory data were collected from the patient’s medical records. Polymorphism typing of TNF-α rs361525 and rs1800629 and IL-10 rs1800872 and rs1800871 were obtained using MALDI-TOF MS. IL-10 rs1800896 and IL-6 rs1800795 were typed using a quantitative real-time polymerase chain reaction. Results: The results of age, HbA1c, fasting glucose, and arterial hypertension are significantly associated in every group. The TNF-α rs1800629A allele and TNF-α rs1800629G/A genotype were associated with microvascular complications and DR. For IL-10-rs1800896, all the models were associated in DKD. The TNF-α rs361525-rs1800629GA haplotype was associated with microvascular complications and DR, while the IL-10 haplotype, rs1800872-rs1800871-rs1800896 GGC, showed susceptibility in every group. Conclusions: Our results show the contributions of the variants of these cytokines to these microvascular complications, but more studies are required to reach relevant conclusions.